2002
DOI: 10.1097/00007890-200212270-00007
|View full text |Cite
|
Sign up to set email alerts
|

Human islet transplantation from pancreases with prolonged cold ischemia using additional preservation by the two-layer (UW solution/perfluorochemical) cold-storage method

Abstract: Improvements in methods to preserve and recover ischemically damaged human pancreases before islet isolation and transplant could be extremely beneficial to the field of clinical islet transplantation. This preliminary study shows that additional short preservation by the two-layer (UW/PFC) cold-storage method can significantly improve islet recovery and increase opportunities of islet transplantation from human pancreases after prolonged cold ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 0 publications
3
96
1
Order By: Relevance
“…Matsumoto et al (26) showed that human islet function, using an in vivo nude mouse transplant bioassay, have resulted in a 67% islet isolation success rate despite the use of a remote islet isolation center (22). Tsujimura was the same between two BMI groups; group 1 were BMI of 30 or more and group 2 were BMI of less than et al (43,44) reported that the overall islet recovery from pancreas preserved using two-layer method is signifi-30. However, Benhamou et al…”
Section: Influence Of Donor-related Parameters On the In Vivo Functiomentioning
confidence: 75%
“…Matsumoto et al (26) showed that human islet function, using an in vivo nude mouse transplant bioassay, have resulted in a 67% islet isolation success rate despite the use of a remote islet isolation center (22). Tsujimura was the same between two BMI groups; group 1 were BMI of 30 or more and group 2 were BMI of less than et al (43,44) reported that the overall islet recovery from pancreas preserved using two-layer method is signifi-30. However, Benhamou et al…”
Section: Influence Of Donor-related Parameters On the In Vivo Functiomentioning
confidence: 75%
“…Nevertheless, inspite of prolonged cold ischemia time significantly more islets could be isolated and recovered after culture compared to storage in UWS (Matsumoto et al, 2002a). These promising results could be confirmed in a similar setting by achieving a significantly higher islet transplantation rate of 71% in pancreases that were oxygenated for additionally 3 hours compared to UWS storage alone (36%) (Tsujimura et al, 2002a). An even more impressing improvement of the success rate from 11% to 53% was obtained in TLM-oxygenated pancreases from marginal donors older than 50 years (Ricordi et al, 2003).…”
Section: Pancreas Oxygenation For Subsequent Islet Transplantationmentioning
confidence: 82%
“…As reported, this was the case for the studies from the Edmonton group (Tsujimura et al, 2002a, Tsujimura et al, 2004a, Salehi et al, 2006, Kin et al, 2006a but not for the study from the Nordic Network (Caballero-Corbalan et al, 2007). This is of particular relevance when pancreases from obese donors are recovered.…”
Section: Pancreas Oxygenation For Subsequent Islet Transplantationmentioning
confidence: 86%
See 1 more Smart Citation
“…[36][37][38] Hypothermia has also been used to add to the preservation of the organs in transplantation, even in the case of pancreas transplantation, on account of decreased organ metabolism. 39,40 Several experimental studies showed an attenuation in ischemia and reperfusion injury, in different organs (liver, lung, neuron), with hypothermia in different degrees. [17][18][19][20][21] Hypothermia was also used as a stimulating factor for the production of heat shock proteins, that showed a prophylactic protection of organ lesions including ischemia and reperfusion injury and acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%